Factors influencing primary immunisation in and around Davangere District: hospital based study - D. V., Veeresh Babu; S., Latha G.; P., Mallikarjuna G. (International Journal of Contemporary Pediatrics, 2017)
Background: Infectious diseases are major cause of mortality and morbidity in children. Immunisation is one of the cost effective and easy method of child survival. Universal immunisation of children against a common vaccine preventable diseases have been a goal of universal immunisation programme, but it remains to be done currently. Success of immunisation programme depends on understanding of the reasons for not immunizing a child, so present study was undertaken. The objective of present study was to find out the immunisation status and various reasons for partial or non-immunisation of child to assess the factors associated with immunisation. Methods: The present study was undertaken in the pediatric OPD of medical college hospital among children(n=194) in the age group of 12 to 60 months. Parents of 194 children were interviewed using preformed study proforma. Children were labelled as completely immunised, partially immunised, or non-immunised according to working definition. Various socioeconomic, demographic, cultural and behavioural factors found to influence immunisation status were outlined. Statistical analysis was done by using chi-square test, p value observed, <0.05 is considered significant. Results: There were 147 children’s (75.8%) who were completely immunised and 41 (21.1 %) partially immunised and 6 (3.1%) were non immunised. Immunisation status was significantly influenced by education of parents, type of family, socio economic status, place of delivery, distance of vaccination centre and locality. Sex of child and birth order has no impact. Most common reasons for partial immunisation (n=41) were education of parents (17%), rural children (23%), socioeconomic status (14%), place of delivery (28.8%), not advised by health worker (29%). Reasons for non-immunisation were (n=6) place of delivery (home=19%), non-availability of immunisation card (10%). Conclusions: The various factors found to influence the immunisation status of children need to address in order to achieve millennium development goal of reducing under five child mortality.